The effect of extrinsic cues on consumer perception: A study using milk tea products. (January 2019) - Choi, Yoonkyung; Lee, Jeehyun
Highlights: The extrinsic cues influenced consumers' liking based on previous consumption. The sample configurations were similar between the intrinsic and extrinsic sessions. Consumers' familiarity of products and terms may affect discrimination ability. Consumers can use a large number of CATA terms to evaluate products with complex flavor. Abstract: Consumers' acceptability may be affected by extrinsic factors as well as intrinsic sensory characteristics. The aims of this study were to determine the influence of extrinsic cues on consumers' acceptance and flavor perception, to examine the discrimination ability of the check-all-that-apply (CATA) method for consumer evaluation, and to investigate possibility of using CATA for complex flavor products and many terms using commercial milk tea products as samples. A total of 240 consumers evaluated eight ready-to-drink milk tea samples in both intrinsic and extrinsic conditions. Participants rated overall liking, and liking and intensities of three dominant characteristics: sweetness, milk flavor, and black tea flavor, and selected attributes that they perceived among 93 CATA terms provided to them. Although extrinsic information on packaging positively influenced acceptability of liked samples, it did not change the preference for tasted samples. However, change in acceptability in the extrinsic evaluation differed between consumers who had previously consumed the particular product and those who had not. Correspondence analysis indicated that the intrinsic and extrinsic evaluations resulted in similar sample and term configurations. Consumers were able to use a large number of terms and distinguished among complex flavor samples using CATA method and intensity differences were shown with varying level of frequency. Reduction of terms was also possible based on the frequency data obtained from consumer evaluation using CATA method. Thus CATA evaluation could be considered for various food categories that sensory terms have not been developed previously.